The effectiveness of gabion type retaining wall made of tire buffer to mitigate slope failure - Ahmad Izzat Asyraf, Yusof (2019)
Retaining wall is one of the way to prevent slope failure. There are many type of retaining wall that have been used. One of them is gabion type retaining wall. Gabion wall is proven as an effective structure to ensure slope stability. In this study, the gabion wall was made from mixture of gravel and tire buffer to study the potential of its usage. The main objective of this study is to replace the gravel in gabion wall with tire buffer. This study used various slope angles which was 30º, 45º and 60º to find the critical angle due effect of precipitation. This study also analyse the effectiveness of slope treatment using gabion wall replace with various proportion of 0%, 20%, 50%, 80% and 100% of tires buffer in term of volume. Slope simulator model in scale 1:20 have been constructed and gabion wall were used to sustain the slope model consist of sand with 60º of critical angle. Moderate rain intensity (13mm/hour) was subjected on the slope and transducer reading that recording the displacement of gabion wall was taken. The result shows that the displacement between of gabion wall with 20% of tire buffer and 100% gravel has a huge difference in resisting slope. Therefore tire buffer is not effective to use as alternative material for gravel in constructing of gabion wall due the large difference of displacement. Therefore, further study need to be constructed to studies the potential of the tire buffer to be utilize in gabion wall in future.